Metabolic profiles revealed synergistically antidepressant effects of lilies and Rhizoma Anemarrhenae in a rat model of depression. (24th January 2017) - Du, Hongli; Zhao, Hongxia; Lai, Xueli; Lin, Qishan; Zhu, Zhenyu; Chai, Yifeng; Lou, Ziyang
Abstract: Depression is a major cause of illness and disability. We applied untargeted metabolomics using mass spectrometry to identify metabolic signatures associated with depression in serum and explored the antidepressant effects of lilies and Rhizoma Anemarrhenae on an experimental model of chronic unpredictable mild stress (CUMS). Meanwhile metabolomics based on UHPLC‐Q‐TOF‐MS was used to study the change in metabolites in CUMS rat serum and to evaluate the effects of Rhizoma Anemarrhenae and lilies (alone and in combination). Partial least squares‐discriminant analysis identified 30 metabolites as decisive marker compounds that discriminated the CUMS rats and the control rats. The majority of these metabolites were involved in amino acid metabolism, the tricarboxylic acid cycle, and phosphoglyceride metabolism. The reliability of the metabolites was evaluated by the administration of lilies, Rhizoma Anemarrhenae, fluoxetine and the combination of lilies and Rhizoma Anemarrhenae to the CUMS rats. Behavior studies demonstrated that treatment with the combination of lilies and Rhizoma Anemarrhenae resulted in optimal antidepressant effects. The combination treatment was almost as effective as fluoxetine. Our results suggest that lilies and Rhizoma Anemarrhenae demonstrate synergistically antidepressant effects in CUMS via the regulation of multiple metabolic pathways. These findings provide insight into the pathophysiological mechanisms underlying CUMS and suggest innovative and effective treatments for this disorder.